GAMBARAN PERILAKU KELUARGA DALAM PENYEDIAAN MAKAN PADA LANSIA DI DESA AEK NABARA TONGA KECAMATAN AEK NABARA BARUMUN KABUPATEN PADANG LAWAS - Nurmaida Sari Tanjung; Ernawati Nasution; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
The elderly need attention and support from family for adaptation on any changes and deterioration that happened in the aging process because family is the main support system for those elderly. The role of family is needed for those elderly in order to fulfill their nutrition intake. In order to fulfill elderly nutrition intake, family shall provide it and prepare food. This kind of study that used descriptive method with cross sectional design, that purpose to know the family’s behavior in providing food to the elderly and to know sufficiently nutrition level of elderly in Desa Aek Nabara Tonga Kecamatan Aek Nabara Barumun Kabupaten Padang Lawas. The primary data for this study were obtained by distributing questionnaires family characteristic, knowledge, behavior, food and nutrition intake preparation. The secondary data were obtained from general description of the Desa Aek Nabara Tonga. The result of this study showed that family knowledge level in supplying food for those elderly mostly categorized in moderate rate noted 86,8%, in supply food for the elderly is categorized shortage noted 73,9% and 26,1% is moderate. The family’s behavior in supplying the food mostly is categorized moderate note about 73,6%, but in supplying the food of the elderly shortage note 82,1% and 17,9% is categorized moderate in supplying the foods. In supplying food for the elderly most in shortage category noted 64,2%. The rate of sufficientcy nutrition mostly on defecient such as energy noted 52,8% . The rate of sufficiently to dissolve vitamin in fat mostly on moderate such as category vitamin A (88,7%), moderate vitamin D (83%). The rate of sufficiently to dissolve vitamin in water such as most in moderate C (90,6%). The sufficient rate of mineral mostly is categorized moderate calcium (50,9%), and most in shortage (49,1%). It is suggested to elderly family their consumption harvest such as vegetables and fruits shuld be priority for family’s requirement. Keywords : Family behavior, sufficient in nutrition, elderly.